Interdisciplinary studies on Coxiella burnetii: From molecular to cellular, to host, to one health research - Benjamin U. Bauer; Michael R. Knittler; Jennifer Andrack; Christian Berens; Amely Campe; Bahne Christiansen; Akinyemi M. Fasemore; Silke F. Fischer; Martin Ganter; Sophia Körner; Gustavo R. Makert; Svea Matthiesen; et al. (Elsevier, 2023)
The Q-GAPS (Q fever GermAn interdisciplinary Program for reSearch) consortium was launched in 2017 as a German consortium of more than 20 scientists with exceptional expertise, competence, and substantial knowledge in the field of the Q fever pathogen Coxiella (C.) burnetii. C. burnetii exemplifies as a zoonotic pathogen the challenges of zoonotic disease control and prophylaxis in human, animal, and environmental settings in a One Health approach. An interdisciplinary approach to studying the pathogen is essential to address unresolved questions about the epidemiology, immunology, pathogenesis, surveillance, and control of C. burnetii. In more than five years, Q-GAPS has provided new insights into pathogenicity and interaction with host defense mechanisms. The consortium has also investigated vaccine efficacy and application in animal reservoirs and identified expanded phenotypic and genotypic characteristics of C. burnetii and their epidemiological significance. In addition, conceptual principles for controlling, surveilling, and preventing zoonotic Q fever infections were developed and prepared for specific target groups. All findings have been continuously integrated into a Web-based, interactive, freely accessible knowledge and information platform (www.q-gaps.de), which also contains Q fever guidelines to support public health institutions in controlling and preventing Q fever. In this review, we will summarize our results and show an example of how an interdisciplinary consortium provides knowledge and better tools to control a zoonotic pathogen at the national level.